Experimental evaluation of DC-DC buck converter based on adaptive fuzzy fast terminal synergetic controller - Zahira Anane; Badreddine Babes; Noureddine Hamouda; Omar Fethi Benaouda; Saud Alotaibi; Thabet Alzahrani; Dessalegn Bitew Aeggegn; Sherif S. M. Ghoneim (Scientific Reports)
Abstract This study suggests an enhanced version of the adaptive fuzzy fast terminal synergetic controller (AF-FTSC) for controlling the uncertain DC/DC buck converter based on the synergetic theory of control (STC) and newly developed terminal attractor technique (TAT). The benefits of the proposed SC algorithm involve the features of finite-time convergence, unaffected by parameter variations, and chattering-free phenomenon. A type-1 fuzzy logic system (T1-FLS) make the considered controller more robust and is utilized to estimate the undefined converter nonlinear dynamics without resorting to the usual linearization and simplifications of the converter model. Taking a switching DC-DC buck converter as a demonstration, the suggested AF-FTSC is thoroughly analyzed and executed on a dSPACE ds1103 controller board. The outcomes of the experiment confirm the competence and applicability of the suggested regulator.